Contact allergens induce CD8+ T cell‐derived interleukin 10 that appears dispensable for regulation of contact hypersensitivity. Issue 5 (2nd March 2017) - Dolch, Anja; Kunz, Stefanie; Dorn, Britta; Roers, Axel; Martin, Stefan F.; Jakob, Thilo
Abstract: Interleukin 10 (IL‐10) has been implied in the regulation of allergic contact dermatitis. Using transcriptional reporter mice we analyzed cellular sources of IL‐10 during contact hypersensitivity (CHS) and identified IL‐10 expressing CD8 + T cells in the skin that are antigen‐specific, display PD‐1, an effector memory phenotype, and IL‐10 expression comparable to that of CD4 + T cells. However, in mice with a selective IL‐10 deficiency in CD8 + T cells CHS responses were comparable to that of controls, even in the absence of CD4 + cells, suggesting that CD8 + T cell‐derived IL‐10 does not contribute significantly to the resolution of CHS responses.